The Legal and Institutional Challenges Facing Community-Based Disaster Management in Tanzania (Tanzania Journal for Population studies and Development, 2024)
This article examines the legal and institutional challenges facing community- based disaster management in Tanzania. This study employed qualitative methods to analyse the legislative and institutional framework governing disaster management in Tanzania. Data was gathered through interviews and focused group discussions with stakeholders engaged in disaster management in Tanzania. The study results indicate that government actors acknowledge the significance of community-based disaster management. However, the integration of local communities in the disaster management process is impeded by various legal and institutional challenges. There exists a notable discrepancy between the policy and legislation governing disaster management. Additionally, the allocation of funds for disaster management is limited, and the avenues for public participation are ineffective. The requirement for sufficient integration of local communities is necessary to foster community-based disaster management. The study suggests a range of legal and institutional changes to improve the integration of communities in the disaster management process. These proposed reforms include legal empowerment of local communities, acknowledging the value of indigenous knowledge, strengthening disaster management committees by offering financial assistance and promoting greater involvement of the civil society.